Pengaruh Pengembangan Karir terhadap Komitmen Organisasi: Systematic Literature Review - Larasati HaningTiyas; Afifatul Khoeriyah; Mohammad Bagus Alfinnur; Dani Rizana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to conduct a Systematic Literature Review (SLR) regarding the influence of career development on organizational commitment. Based on the analysis of various scientific articles, career development is an important approach in human resource management, which focuses on improving employees’ skills, enthusiasm, and readiness to face job challenges and promotion opportunities. On the other hand, organizational commitment refers to the emotional connection that employees have with their workplace, which includes aspects of emotional attachment, obligation, and enduring bonds. The results of the systematic literature review indicate that many previous studies have found a strong and positive correlation between career development and organizational commitment. Workers who are aware of support for their career development, including training programs, mentoring, or predetermined career paths, generally show a higher level of dedication to their organization. Furthermore, various studies have shown that career development can also have an indirect effect on organizational commitment through mediating factors such as job satisfaction, work motivation, and employee performance. However, several studies have shown that career development does not always have a significant impact on organizational commitment, particularly in organizations without a structured career system or when employees have negative perceptions of career opportunities. These varying results highlight the existence of contextual factors that influence the relationship between variables. Overall, this study offers in-depth insights into the significance of career development as a strategic factor in enhancing organizational commitment, along with suggestions for organizations and future researchers conducting similar studies.